g EFFECT OF VIBRATION-CORROSION ON ALUMINUM ALLOY(DIN1100) THAT WELDED BY TIG TECHNIQUE AND OPERATING IN THE MARINE ENVIRONMENT: abstract, introduction, mathematical and experimental models, results and discussion, conclusions (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
In this research studied the effect of corrosion in presence of vibration on aluminum alloy type (DIN1100) operating in sea water (3.5% NaCl) and compared these results with the same alloy after it was welded by TIG technique at the same vibrated corrosive medium, addition to study the corrosion in static medium for welded and non- welded alloy, then comparison between the four cases depending on corrosion rates and microstructures it was noted that ;the greatest percentage of corrosion rate was 43% of welded alloy at vibration-corrosion and least percentage of corrosion rate was 8% of non-welded alloy at static corrosion.